Reduction of systemic error of measuring of horizontal constituents of speed vector by Doppler log carrier - Baras, S. T.; Martyniuk, A. P. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The algorithm of compensation of influence of vertical constituent of speed vector on operation of Doppler log is considered. Mathematical dependences which confirm the substantial reduction of error of measuring of horizontal constituents of speed vector are obtained. Errors are calculated and their graphic dependences are suggested.